2011
DOI: 10.4314/bajopas.v4i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence of Cytomegalo Virus Antibodies in Pregnant Women Attending Two Selected Hospitals in Sokoto State, North-Western Nigeria

Abstract: Infection with cytomegalo virus (CMV), especially in pregnancy may cause pregnancy complications such as congenital infection, non-hereditary deafness, intrauterine growth restriction and other high defects. This study was to evaluate the prevalence of CMV in pregnant women attending Antenatal Clinics at Maryam Abacha Women and Children Hospital (MAWCH) and Sokoto Specialist Hospital (SSH). The study enrolled 90 pregnant women (age range: 16-45 years old) and data on demographic and life styles obtained using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
5
7
4
Order By: Relevance
“…The present study shows a high CMV IgG overall seroprevalence (92.1%), with no significant differences between rate in women with BOH and that with normal pregnancy. Thus the susceptibility rate in our study population was 7.9%, which was higher to that reported recently for Turkey [11], [17]- [22], Nigeria [23], [24], Brazil [25], Iran [26], [27], Bangladesh [28], Korea [29], and Cuba [30]. However, our study susceptibility was lower than that reported for France [31], Nepal [32], India [13], [33], [34], Switzerland [35], Croatia [36], Malaysia [37], Iran [12], [38], Poland [39], Ireland [10], Russia [40], Taiwan [41], Germany [42], Azerbaijan [43], Bangladesh [44], and Brazil [45].…”
Section: Discussioncontrasting
confidence: 66%
“…The present study shows a high CMV IgG overall seroprevalence (92.1%), with no significant differences between rate in women with BOH and that with normal pregnancy. Thus the susceptibility rate in our study population was 7.9%, which was higher to that reported recently for Turkey [11], [17]- [22], Nigeria [23], [24], Brazil [25], Iran [26], [27], Bangladesh [28], Korea [29], and Cuba [30]. However, our study susceptibility was lower than that reported for France [31], Nepal [32], India [13], [33], [34], Switzerland [35], Croatia [36], Malaysia [37], Iran [12], [38], Poland [39], Ireland [10], Russia [40], Taiwan [41], Germany [42], Azerbaijan [43], Bangladesh [44], and Brazil [45].…”
Section: Discussioncontrasting
confidence: 66%
“…The level of maternal immunity observed in this study substantiates previous studies in Nigeria and other developing countries. [9][10][11] This however differs from those reported for developed countries where seroprevalence rates were lower. 12,13 The differences in the prevalence of maternal CMV infection between the developed and developing countries may reflect the low hygienic standard and cultural practices that propagate disease transmission in developing countries.…”
Section: Discussionmentioning
confidence: 89%
“…In Asian countries such as Malaysia, the seroprevalence of CMV IgG antibodies among pregnant women was reported to be 84.0% [13]. In Nigeria, serological survey conducted in Bida, Lagos and Sokoto among pregnant women found a seroprevalence of 84.2%, 97.2% and 98.7% respectively [9,14,15]. These results shows that CMV is on the rise in Nigerria.…”
Section: Introdcutionmentioning
confidence: 99%